2018
DOI: 10.1097/md.0000000000009227
|View full text |Cite
|
Sign up to set email alerts
|

Changes in attitudes, risky practices, and HIV and syphilis prevalence among female sex workers in Brazil from 2009 to 2016

Abstract: Background:The present study aims at investigating the progress made toward controlling the human immunodeficiency virus (HIV)/AIDS epidemic among female sex workers (FSW) from 2009 to 2016.Methods:The baseline of respondent-driven sampling (RDS) study among FSW was carried out in 2009, in 10 Brazilian municipalities. In 2016, information on FSW were collected in 12 municipalities. The analyses took into account the dependence among observations, resulting from the recruitment chains, and the unequal probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 33 publications
2
25
0
2
Order By: Relevance
“…Studies have shown epidemiological heterogeneity on the prevalence of STIs among different regions of Brazil [7,8]. A survey conducted in 10 different state capital cities in Brazil (the seat of a state government, in this case with an average large metropolitan area > 1.5 million inhabitants) showed an increase from 2.4% in 2009 to 8.5% in 2016 on the prevalence of syphilis among FSWs, which demonstrates that beside all health public policies and access to information available, the prevalence of syphilis is rising [9]. Another study carried out in three southern cities of Brazil (Tubarão, Laguna and Imbituba), showed an even higher prevalence of syphilis among FSWs (19.7%) [8].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies have shown epidemiological heterogeneity on the prevalence of STIs among different regions of Brazil [7,8]. A survey conducted in 10 different state capital cities in Brazil (the seat of a state government, in this case with an average large metropolitan area > 1.5 million inhabitants) showed an increase from 2.4% in 2009 to 8.5% in 2016 on the prevalence of syphilis among FSWs, which demonstrates that beside all health public policies and access to information available, the prevalence of syphilis is rising [9]. Another study carried out in three southern cities of Brazil (Tubarão, Laguna and Imbituba), showed an even higher prevalence of syphilis among FSWs (19.7%) [8].…”
Section: Introductionmentioning
confidence: 91%
“…These cities can be characterized as small urban areas (population is between 50,000 and 200,000), showing about 100,000 inhabitants, have human development indexes around 0.55 (low) and have as their main economic activities: fishing, agriculture, extraction and processing of natural resources, such as crabs, shrimps and kaolin (used in the production of alumina and aluminium). All these cities have an intense flow of people and product trade, mainly by highways and seaports [9]. The following inclusion criteria were used: women (biologically determined at birth) older than 15 years who reported commercial sex at least once in the last 3 months that agreed to participate in the study and signed the free consent form.…”
Section: Study Design and Ethical Aspectsmentioning
confidence: 99%
“…The comparison of biological and behavioral studies performed in 2009 and 2016 in the group of FSWs showed an important increase of the HIV testing coverage in Brazil. The proportion of FSWs tested for HIV at least once in life grew from 64.4% to 77.3%, while the testing coverage in the 12 months prior to the researches increased from 20.3% to 39.3% 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The combined prevalence was estimated in 5.1%. In a biological and behavioral survey conducted in 10 Brazilian cities, in 2009, the prevalence of HIV was estimated in 5% 14 , and in a survey of 2016, performed with similar methodology, the prevalence of HIV remained in the same level 15 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Assessing one's knowledge, attitudes and performance are necessary prior to AIDS preventive planning. 6 we decided that knowledge would be addressed in a construct called 'health literacy.' In fact, health literacy refers to one's capacity to receive, perceive and interpret primary information and health services, which are required for appropriate decision-making.…”
Section: Introductionmentioning
confidence: 99%